Exploring Trust Dynamics in Islamic Insurance Company - Abdul Halim; Tubagus Ismail; Faizul Mubarok (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
This paper examines the determinants of customer trust in Islamic insurance agents in Bumida Islamic Unit Insurance. An online questionnaire that included information on customers' views of Islamic insurance agents was used to collect data from all Bumida Islamic Unit Insurance branch offices. The Structural Equation Models with Partial Least Square (SEM-PLS) approach is used for quantitative analysis. The primary data used in this research was obtained from 60 respondents from some Islamic branches of Bumida Islamic Unit Insurance. It was found that communication, expertise, and image determine customers' trust in Islamic insurance agents on Bumida Islamic Unit Insurance's significant values. These findings support the previous research findings on this issue. Customer trust in Islamic insurance agents is essential, but more is needed to construct customer trust. This research proposes a new perspective on what determines the trust of insurance customers in Islamic insurance agents.